ANALISIS PENDAPATAN USAHATANI KELAPA DI KECAMATAN BANTANKABUPATEN BENGKALIS - Novia Marlina; Djaimi Bakce; Novian Novian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Bantan Subdistrict is the center of coconut production in Bengkalis Regency, however the land area and coconut production tend to decrease every year coconut cultivation tehcniques are not in accordance with the standards are one of the factors causing the production of coconut production in Bantan Subdistrict. The purpose of this study was to determine coconut cultivation techniques, and analyze the income of coconut farming. The methode used is descirptive and analysis of farm income. Respondents consisted of 30 coconut farmers. The result of the analysis of coconut cultivation techniques in Bantan Subdistrict is not in accordance with the recommendations, andthe farming income is still relatively small.Keywords: Bantan Subdistrict, coconut, Income